Japan's Shifting Status in the World and the Development of Japan's Medical Insurance Systems - Sugita, Yoneyuki (Springer Nature Singapore : Imprint: Springer, 2019)
This book explains the origins and early developments of Japanese medical insurance systems from the 1920s to the 1950s. It closely examines the changes in the systems and the symbiotic relationship between Japan's status in international relations and the development of domestic medical insurance systems. While previous studies have regarded the origins and development of Japanese medical insurance systems as merely a domestic issue and pay little attention to the role or effects of international affairs, this book closely examines the changes in these systems by looking at the enactment of the Health Insurance Law in 1922, the establishment of the National Health Insurance in 1938, the epoch-making reforms of 1942, numerous plans in the early Allied occupation period, and Japan's social security plan in 1950. In doing so, it shows that there was indeed a symbiotic relationship between Japan's status in international relations and the changing nature of domestic medical insurance systems. It also reveals that Japan's status in international relations set the framework within which interested groups, primarily the government, made rational choices. This book is a valuable resource for academics, researchers and students who have an interest in the Japanese medical insurance systems.